On the legal issues of providing care services on farms - Krzysztofik-Pelka, Magdalena (Przegląd Prawa Rolnego, 2022)
The aim of the article is to characterise care farms and define their legal status. First, the concept of a multifunctional development of agricultural farms is defined, and then the manner in which care farms influence the concept of multifunctionality determined. It was also necessary to place a care farm in the system of social agriculture. The common regulations of the EU Member States adopted to support care services in farms have also been presented. Further considerations focus on the identification of documents which pointed out to the need to undertake activities aimed at the creation and development of care farms in Poland. Projects that are already implemented, particularly those co-financed from EU funds, are presented. An attempt is also made to answer the question whether care farms should be regulated in a separate legislative act or whether relevant provisions should be inserted in some already existing act. Another question concerns the manner in which care farms should be financially supported.